(3JShjb GdeYdheGJ (B/s - (3YdjGf, QHMj eUWais; (3GdSGeQGfj, GjeGf aGVd s ((3YeGf(B: s (3OGQ UaGA ddfT hGdJhRjY(B, s, 2004)
(3JShjb GdeYdheGJ (B((3eaGgje CSGSjI(B)- (3HjFI JShjb GdeYdheGJ(B- (3GdJShjb aj GdeDSSGJ GdeYdheGJjI(B- (3JShjb GdNOeGJ aj GdeDSSGJ GdeYdheGJjI(B- (3JLRFI GdShb GdeSJgOaI hGdeRjL GdJShjbj(B- (3GSJQGJjLjI JShjb GdeYdheGJ(B- (3GdYdGbGJ GdYGeI aj NOeI GdYedjI GdJShjbjI(B- (3GdJShjb YHQ GdCfJQfJ(B- (3HMhK GdJShjbs
Keywords: (3GdeYdheGJs; (3HK GdeYdheGJs; (3JShjb GdeYdheGJs